Immediate and delayed autologous abdominal microvascular flap breast reconstruction in patients receiving adjuvant, neoadjuvant or no radiotherapy: A meta‐analysis of clinical and quality‐of‐life outcomes - Khajuria, A; Charles, W; Prokopenko, M; Beswick, A; Pusic, A; Mosahebi, A; Dodwell, D; Winters, Z (Wiley, 2019)
Background: Effects of postmastectomy radiotherapy (PMRT) on autologous breast reconstruction (BRR) are controversial regarding surgical complications, cosmetic appearance and quality of life (QOL). This systematic review evaluated these outcomes after abdominal free flap reconstruction in patients undergoing postoperative adjuvant radiotherapy (PMRT), preoperative radiotherapy (neoadjuvant radiotherapy) and no radiotherapy, aiming to establish evidence‐based optimal timings for radiotherapy and BRR to guide contemporary management.